2005
DOI: 10.1096/fj.05-4342fje
|View full text |Cite
|
Sign up to set email alerts
|

Expression of toll‐like receptors by human muscle cells in vitro and in vivo: TLR3 is highly expressed in inflammatory and HIV myopathies, mediates IL‐8 release, and up‐regulation of NKG2D‐ligands

Abstract: The particular microenvironment of the skeletal muscle can be the site of complex immune reactions. Toll-like receptors (TLRs) mediate inflammatory stimuli from pathogens and endogenous danger signals and link the innate and adaptive immune system. We investigated innate immune responses in human muscle. Analyzing TLR1-9 mRNA in cultured myoblasts and rhabdomyosarcoma cells, we found constitutive expression of TLR3. The TLR3 ligand Poly (I:C), a synthetic analog of dsRNA, and IFN-gamma increased TLR3 levels. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 63 publications
(82 reference statements)
5
62
0
5
Order By: Relevance
“…Recent publications have shown that cell expression of NKG2D ligands was induced by signaling through TLRs (51,52). There is accumulated evidence that human placenta expresses TLR-2, TLR-3, and TLR-4 (53).…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have shown that cell expression of NKG2D ligands was induced by signaling through TLRs (51,52). There is accumulated evidence that human placenta expresses TLR-2, TLR-3, and TLR-4 (53).…”
Section: Discussionmentioning
confidence: 99%
“…20 Interleukin-6 (IL-6) production in response to lipopolysaccharide by human 21 and murine 22 myoblasts suggested that skeletal muscle cells express specific TLRs. 23,24 As a matter of fact, the expression of TLR2, involved in the response to peptidoglycan and lipoproteins/lipopeptides, 25 TLR4, which recognizes LPS from Gram-negative bacteria, 24 TLR5, which recognizes flagellin from Gram-negative outer membrane, 26 TLR3, which recognizes double-stranded (ds) RNA, suggesting a role in viral recognition, 27 and TLR9, which recognizes unmethylated CpG oligodeoxynucleotides, DNA motifs that are found more commonly in bacterial and viral genomes has been demonstrated ( Figure 1a). 25 TLR2, TLR4, TLR5 and TLR9 mRNA expression has been found in murine differentiated myotubes as well as in muscles; interestingly, TLR2 and TLR5 were expressed only in murine differentiated myotubes, but not in myoblasts, indicating that the expression of these TLRs is regulated by skeletal muscle cell differentiation.…”
Section: Toll-like Receptor Function In Muscle Cellsmentioning
confidence: 99%
“…29 The stimulation with Poli(I:C) (an analogue of dsRNA) and interferon-g (IFN-g) upregulates the expression of TLR-3 mRNA in cultured human myoblasts, inducing nuclear factor-kB activation and IL-8 secretion; TLR3 was also detected in biopsies from inflamed and non-inflamed human muscles. 23 TLRs may therefore represent the immune trigger following DNA injection in muscles: vector CpG motifs can act as adjuvants similarly to bacterial CpG, inducing activation of professional APCs, while directly stimulating muscle cell-mediated immune response. 30 Mammalian, bacterial, plasmid and synthetic DNA containing unmethylated CpG dinucleotides in specific sequence contexts are recognized by TLR9 on B cells and on plasmacytoid DCs, triggering IL-12, tumour necrosis factor (TNF)a and IFNa secretion, a critical step in cellular immune response.…”
Section: Toll-like Receptor Function In Muscle Cellsmentioning
confidence: 99%
“…In human skeletal muscle cell lines such as myoblasts and human rhabdomyosarcoma cells (TE671), there are low mRNA expression of TLR1-7 and TLR9 but constitutively expression of TLR3 which can be up-regulated by poly(I : C) [90]. Moreover, TLR3 engagement with poly(I : C) or other dsRNA is capable of initiating the increase of NKG2D on NK cells, and also the up-regulation of respective ligands such as MICA, MICB, ULBP-2 and ULBP-3 in human muscle cells [91].…”
Section: The Crosstalk Between Tlr and Nk Cell Receptorsmentioning
confidence: 99%
“…Moreover, TLR3 engagement with poly(I : C) or other dsRNA is capable of initiating the increase of NKG2D on NK cells, and also the up-regulation of respective ligands such as MICA, MICB, ULBP-2 and ULBP-3 in human muscle cells [91]. The interaction between NKG2D and ligands results in autologous cytotoxicity and the secretion of IL-8 and tissue inhibitor of metalloproteinase-2 (TIMP-2), which can aggravate the development of sarcolysis [90]. The activation of TLR signaling also breaks down epithelial homeostasis of small intestine in mice.…”
Section: The Crosstalk Between Tlr and Nk Cell Receptorsmentioning
confidence: 99%